PERANCANGAN DAN IMPLEMENTASI APLIKASI BANTU TICKETING STUDI KASUS IT USER SUPPORT PT. XYZ - Budiman . (LPPM UNIBI, 2019)
The utilization of information technology is increasingly growing, company or organization alreadytransformed using information technology support the business processes of each. The higher the use ofinformation technology, the more vulnerable a company experiencing problems in utilizing informationtechnology devices, with the existence of the problem then it needs power IT User Support. XYZ Companyis a company that has a computerized system in the running of all activities. XYZ Company can havebranches, where each branch offices can communicate through computer networks between branch officesor headquarters. In case of damage or disruption to your computer or the network in each branch officewill be easier for the IT User Support to follow up on the corresponding section in the Division ofinformation technology. Application Help Ticketing for IT User Support aiming at improving service andperformance of the IT User Support in dealing with trouble shooting. The importance of the IT User Supportis making the alignment on the workload that fair and balanced, while it also as a tool for assessment ateach technician. With the design and implementation of these systems can alleviate the performance ofUser Support, IT can be noted the performance of the IT User Support, and view graphs of the developmentof the performance of the IT User Support.